Evolution of Milk Consumption and Its Psychological Determinants: A Mini-Review - Castellini, Greta; Graffigna, Guendalina (Frontiers in Nutrition, 2022)
The consumption of lactose-free products and in particular lactose-free milk is increasing worldwide. Although many studies claim that this dietary trend is mainly determined by the number of lactose intolerant people that is growing, others state that most of them self-report an intolerance that has not been diagnosed by medical tests. However, many researchers reported that the consumption of lactose-free milk may put the consumers’ health at risk especially when the subjects are not intolerant. Consequently, understanding this new dietary trend considering its main determinants it is necessary to generate educational and intervention campaigns useful to guide people towards healthier and more adequate eating styles. For these reasons we conducted a narrative mini review to summarize the factors contributing to the consumption of lactose-free milk as an alternative to cow’s milk, exploring intrinsic and extrinsic product characteristics, biological and physiological, as well as psychological, situational and socio-cultural factors. This narrative mini-review shows that there are six categories of factors that affect the consumption of lactose-free milk. In particular, the intrinsic aspects linked to the product and the socio-demographic characteristics of the consumer are the most explored. On the contrary, situational and socio-cultural factors are the least studied. Finally, this study argues that there are too few studies that investigates the emotional, identity and social aspects underlying these food choices, suggesting the development of future research that investigate the implicit consumer subjective levers to decipher lactose-free milk consumptions.